Sweet Marjoram - Fatemeh Bina PharmD, PhD Candidate; Roja Rahimi PharmD, PhD (SAGE Publishing, 2017)
Origanum majorana L. commonly known as sweet marjoram has been used for variety of diseases in traditional and folklore medicines, including gastrointestinal, ocular, nasopharyngeal, respiratory, cardiac, rheumatologic, and neurological disorders. Essential oil containing monoterpene hydrocarbons and oxygenated monoterpenes as well as phenolic compounds are chemical constituents isolated and detected in O majorana . Wide range of pharmacological activities including antioxidant, hepatoprotective, cardioprotective, anti-platelet, gastroprotective, antibacterial and antifungal, antiprotozoal, antiatherosclerosis, anti-inflammatory, antimetastatic, antitumor, antiulcer, and anticholinesterase inhibitory activities have been reported from this plant in modern medicine. This article summarizes comprehensive information concerning traditional uses, phytochemistry, and pharmacological activities of sweet marjoram.